Financing and valuation of early stage biopharmaceutical companies : Funding R&D projects and challenges in valuations of early stage biopharmaceutical firms in Finland - Manninen, Sakari (fi=Turun yliopisto|en=University of Turku|, 2017)
To keep up acceptable growth, the largest pharmaceutical companies should bring multiple new drugs to the market every year. As they have challenges developing enough new medicines in-house, they are forced to screen for acquisition prospects – small companies developing promising drug candidates until being acquired. As the small companies often have no revenues during this long time period, financing the R&D project up to the acquisition point is challenging. The objective of the study is to answer the following research questions: 1. How do the used sources of financing change by the stage in which the drug development project is? 2. Do capital structures of early stage biopharma companies differ from the optimal capital structures proposed in finance theories, and if they do, how? 3. How is information asymmetry taken into account when discussing investment deals between venture capital firms and early stage biopharmaceutical companies? 4. Do company valuation models proposed in finance theories differ from the actual practices used by the early stage company and the VC side? This study follows a qualitative research approach, and the empirical data was gathered from two half-structured interviews. The first person is responsible for the financial matters of a Finnish early stage biopharmaceutical company that is currently negotiating the financing of the mandatory human trials. The second interviewee is a partner at a Finnish VC firm that is targeting the life-science industry. The results of the interviews were compared to the financing sources, capital structures and valuation methods that earlier academic research proposes to be used in case of early stage biopharmaceutical companies. Based on the results, the used financing sources vary greatly depending on the stage of the project. Universities, foundations, and Tekes are important financiers, but there is a serious lack of private investors investing in drug development projects in Finland. Another finding is that there seems to be no optimal capital structure that an early stage biopharmaceutical firm should try to copy or follow. According to the interviewees, hiring experienced consultants is one of the most important ways of lessening the information asymmetry related challenges related to the investment deals. When looking at the valuation methods that earlier academic papers have proposed for estimating company or project values, the paper points out that there are essentially no best practices for estimating the exact value of a drug development project, as the uncertainties and risks associated with the projects are so high.